Communicating the Improvements Developed from Critical Incident Reports is an Essential Part of CIRS - Hubertus, J.; Piehlmeier, W.; Heinrich, M. (Klinische Pädiatrie, 2016)
Background: The Critical Incident Reporting System (CIRS) is a tool for employees to report anonymously of near misses. Its efficiency and improvement of safety is proved by many studies. Our department introduced CIRS in 2009 and it is used frequently. As the number of reports decreased over time we asked for factors responsible for the reduced use.Methods: All employees had access to CIRS and have been trained in several courses of instruction. Accomplished results and consequences were published in biannual newsletters. In 2014 we initiated an anonymous employee attitude survey to ask for their experience and satisfaction with CIRS.Results: 88 near misses were reported since 2009. 44 (50%) reports were classified as RS1, 34 (38.6%) as RS2, and 10 (11.4%) as RS3. No RS4 reports were notified. Most reports concerned problems with administration of medication (n=26; 29.5%) and problems with technical devices (n=18; 20.5%). 75 (83%) of our employees participated in the survey. 64 (86.5%) discerned that CIRS is anonymous. 31 (41.9%) reported already a near miss. Of note, two-third didn’t realize an improvement following their report. On the other hand, only half of the pollees stated to read the newsletter.Conclusion: Even if efficiency and advantages of CIRS are proved and undeniable, sufficient and perpetual feedback of results and improvements developed by the CIRS team and regular trainings of the employees are mandatory for the success of CIRS.
Keywords: CIRS; near misses; survey; critical incidents